2022
DOI: 10.1159/000526240
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Body Mass Index on the Growth Hormone Peak Response regarding Growth Hormone Stimulation Tests in Children

Abstract: Introduction: Several studies have analyzed the association between the maximal growth hormone serum level obtained during a growth hormone stimulation test (GH-Max) and the body mass index standard deviation score (BMI-SDS). However, as sample sizes were quite small, our study aimed to analyze the association between GH-Max and BMI-SDS within a large cohort of 991 children. Further, we investigated other influencing factors, like test type, age, sex, puberty and preterm birth. Methods: Children with short sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…For children, the normal range for BMI changes as children grow and mature over the years. Obesity in children is defined as a BMI > 95th percentile (or +1.6 SDS) ( 159 ). In a meta-analysis by Abawi et al .…”
Section: Individual Patient Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For children, the normal range for BMI changes as children grow and mature over the years. Obesity in children is defined as a BMI > 95th percentile (or +1.6 SDS) ( 159 ). In a meta-analysis by Abawi et al .…”
Section: Individual Patient Considerationsmentioning
confidence: 99%
“…( 160 ), they noted a negative correlation between BMI SDS and peak GH responses to a GH secretagogue, with each increase in BMI-SDS of 1 unit associated with a decrease in GH max of ~12%. Thieme et al ( 161 ) sought to further study that correlation to verify it in a larger cohort of children below the 10th percentile for height for age. In a single center with almost 1000 patients, they showed consistently negative associations between BMI-SDS and the maximal GH level with effect size of about β = −1.1.…”
Section: Individual Patient Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loche et al described the contrary influence of BMI on the GH reply to the clonidine stimulation test (15). In the study by Thieme et al, glucagon and arginine tests showed significant differences in GH peak levels; glucagon tests were found to be approximately 2 ng/mL higher on average than arginine tests (16). It was assumed that these distinctions in the GH peak value were owing to the sort of test used by Secco et al (17).…”
Section: Discussionmentioning
confidence: 99%
“…There are some factors that they might be associated with GH secretion. Studies showed that heat exposure, physical activity, age, gender, body composition, muscle mass, visceral fat, central adiposity, some hormones, blood glucose, and insulin levels influence GH secretion [ 76 , 77 ]. However, the association between body fat, glucose disposal, and GH secretion remains unclear.…”
Section: Discussionmentioning
confidence: 99%